Development of 2,3-butanedione-sensing element using Pt-nanoparticle-decorated tin oxide for health applications - Fotia, A.; Malara, A.; Bonaccorsi, L.; Macario, A.; Gnisci, A.; Frontera, P. (Frontiers in Chemistry, 2025)
An efficient, reliable, and cost-effective sensor of 2,3-butanedione, an organic compound with a distinctive buttery aroma, is here developed through the production of a sensible layer based on a tin oxide semiconductor decorated with platinum nanoparticles. The resulting material is subjected to characterization and testing to evaluate its capability to sense 2,3-butanedione, which is known to be responsible for health risks upon inhalation, including the potential to cause lung disease, and to be detected in the breath of individuals with cystic fibrosis. The results demonstrate that the developed sensor provides high sensitivity and selectivity for 2,3-butanedione in specific experimental conditions, featuring advantages such as simplicity, portability, and rapid response. In addition, it shows great potential for on-site safety and health applications, providing a practical solution for real time monitoring.